The Sioux Chef's Indigenous Kitchen - Sherman, Sean, 1974-; Dooley, Beth (Book collections on Project MUSE., 2017)
Here is real food: indigenous American fruits and vegetables, wild and foraged grains, game, and fish. Locally sourced, seasonal, "clean" ingredients and nose-to-tail cooking are nothing new to Sean Sherman, the Oglala Lakota chef and founder of The Sioux Chef. In his breakout book, The Sioux Chef's Indigenous Kitchen, he shares his approach to creating boldly seasoned foods that are vibrant and healthful, at once elegant and easy. Sherman dispels outdated notions of Native American fare - no fry bread or Indian tacos here - and uses no European staples such as wheat flour, dairy products, sugar, and domestic pork and beef. The Sioux Chef's healthy plates embrace venison and rabbit, river and lake trout, duck, quail, wild turkey, blueberries, sage, sumac, timpsula or wild turnip, plums, purslane, and abundant wildflowers. Contemporary and authentic, his recipes include Cedar-Braised Bison, Griddled Wild Rice Cakes, Amaranth Crackers with Smoked White Bean Paste, Three Sisters Salad, Deviled Duck Eggs, Smoked Turkey Soup, Roasted Corn Sorbet, and Hazelnut-Maple Bites. The Sioux Chef's Indigenous Kitchen is a rich education in and a delectable introduction to modern indigenous cuisine of the Dakota and Minnesota territories, with a vision and approach to food that travels well beyond those borders. -- From page 2 of cover